(untitled) (Journal of Dhaka Medical College, 2021)
Pre – Eclampsia is a disorder of 2nd half of pregnancy, which is characterized by a combination of hypertension, proteinuria and edema, secondary to decreased placental perfusion. Clinical studies suggest that there are morphological changes in the placenta of pre-eclamptic women, compared to normotensive pregnant women. In developing countries, pre-eclampsia causes an estimated 50,000 maternal deaths per year. Only a small number of studies have however, been conducted in Bangladesh. Objective: To compare the morphology of placenta in selected pre-eclamptic and normotensive pregnant women. Methods: 220 pregnant women were selected with inclusion and exclusion criteria from 3 different medical colleges and divided into 2 groups – A study group, consisting of 110 pre-eclamptic women and a control group consisting of 110 normotensive pregnant women. Dietary information was collected by 7 days food frequency questionnaire and food score was determined. Anthropometric and biochemical tests were performed. To measure the weight of the placentas, the decidual part of the placentas were removed. The umbilical cords were then cut, nearest to the placenta, to drain the blood from the placental vessels, and the weight was recorded upto nearest gram with weighing machine. The diameters of placentas were measured by taking the average of two maximum diameters of placentas with measuring tape (cm).The cotyledons were counted from maternal side after removal of deciduas basalis. Number of placental infarcts were counted from fetal side. Results: The mean weights, diameters, number of cotyledons were found to be significantly lower in the study group, compared to the control group. The number of infarcted areas was significantly higher in the placentas of pre-eclamptic women Conclusion: Therefore, weight, diameter and number of cotyledons are decreased and number of infarcted areas are increased in the placenta of pre-eclamptic women, compared to normotensive pregnant women. J Dhaka Medical College, Vol. 29, No.2, October, 2020, Page 171-177